Determinan Kejadian Abortus - Citra Adityarini Safitri; Dian Irawati; Ruchiana (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2026)
Abortion was one of the leading causes of maternal mortality. In early pregnancy, bleeding could occur as a result of abortion. This study aimed to identify the factors associated with the incidence of abortion at Sakinah Islamic Hospital, Mojokerto, in 2023. A case-control design was employed in this study. The sample consisted of 158 cases selected through total sampling and 158 controls selected through simple random sampling. Data were analyzed using the Chi-square test. The results showed that age and history of abortion were significantly associated with the incidence of abortion, as indicated by a p-value of less than 0.05. In contrast, parity was not significantly associated with the incidence of abortion. These findings indicated that maternal age and previous abortion history were important factors related to abortion incidence, whereas parity did not show a significant relationship. Based on these findings, preventive efforts could have included routine antenatal counseling and family planning counseling for couples of reproductive age. These measures were expected to support well-planned pregnancies and reduce the risk of abortion